Plano de projeto: implementação de sistema de gestão da qualidade ISO 9001 na empresa Gajacom Industrial ltda - Schild, Daniel de Menezes (Universidade do Vale do Rio dos Sinos, 2012)
This paper has as main objective to present a project planning to implement a Quality Management System (QMS) in the company Gajacom Industrial Ltda, suitable to the requirements of NBR ISO 9001:2008. The company Gajacom has been working in the market industrial fasteners for 12 years. Because of the strong increase in competition, the company realized the necessity to implement a quality management system to thereby obtain reducing time and cost in their operations and increase their efficiency and effectiveness in their service, thus result in better care of their customers. This final paper explains the Project Management Planning, containing the Management Planning integration, scope, time, costs, quality, resources, communications, risks and procurement necessary to good practice project management and in acoordance with the knowledges described on the PMBOK Guide.
Keywords: Plano de gerenciamento do projeto; Project Management Planning